Optimising forest road planning to maximise the mobilisation of wood biomass resources in Northwest Russia. Issue 4 (4th July 2017) - Havimo, Mikko; Mönkönen, Petteri; Lopatin, Eugene; Dahlin, Bo
ABSTRACT: Forest accessibility is a key factor for the effective mobilisation and utilisation of wood biomass. Therefore, obtaining reliable and precise information is crucial concerning forest resources and the appropriate methods of transportation. The main objective of this study was to improve the methodological approaches to forest road planning to improve the transportation of wood biomass in Russia. The results from the present study into the theoretical optimal road density revealed the importance of economic feasibility and cost-effectiveness when considering expansion of the forest road network. Cost reduction could be achieved through effective operational planning, which should also incorporate the costs for harvesting, road construction and transportation. However, no clear evidence was found regarding the best strategy to apply. The construction of high-quality forest roads should be concentrated in the forests with the largest standing volumes. However, in the near term, extended two-step forest transportation with 6*6WD trucks on the lowest quality roads (e.g. the cheapest basic forest roads) will continue to be an important part of the supply chain; it may even be more cost-efficient to maintain and upgrade these roads to allow all-year-round access with ordinary 6*4WD trucks rather than constructing new roads in these areas. Thus, zoning of the procurement area could be used for optimising forest road planning to maximise the mobilisation of wood biomass.